Pemanfaatan Tanah Hibah Untuk Peningkatan Ekonomi Ditinjau Dari Hukum Ekonomi Syariah - Gaussian, Gini; Mutoharoh, Lala Siti (STAI Al-Musaddadiyah Garut, 2025)
From a social aspect, the use of granted land for religious purposes is very effective, but does not have a positive impact on the community's economy. So, if the Land Grant is not carried out productively, it will not be realized optimally. Grants can be used as a potential economic institution to be developed as long as they can be managed optimally. Therefore, the use of land grants needs serious study and must be reviewed from the aspect of Sharia Economic Law. The type of research used in this research based on the data obtained is qualitative research. It is called qualitative because the problems are unclear, holistic, complex, dynamic and full of meaning, so it is impossible for the social situation data to be captured using quantitative research methods. This research discusses the practice of grants in Sagaranten Village, where this practice occurred in Mrs. Nenok's family in the form of a plot of land and a house which was carried out by her mother in order to minimize disputes between families which was carried out orally and witnessed by all her children and the use was carried out by working on it. by other people with a profit sharing system and if the house is rented for 600 thousand per month. The conclusion of this research is that based on a review of Sharia Economic Law regarding the use of granted land carried out by Mrs. Nenok in her village, from a legal perspective it fulfills the requirements and pillars of the grant both for the goods donated and the recipient of the grant. Also, the utilization practice complies with Sharia Economic Law because it does not there is an element of usury in it. Keywords: Grants; Economic Improvement; Sharia Economic Law;